Reformulation of Post-Divorce Support Arrangements in the Indonesian Family Law System - Indra Satria; Ansari; Arifuddin Muda Harahap (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2025)
This study aims to analyze the regulation of post-divorce maintenance for former wives and children within the Islamic family law system in Indonesia and to formulate a legal reformulation model that provides greater legal certainty and fairer protection. This research employs a normative juridical method using a maqasid sharia approach, supported by empirical analysis of religious court decisions. The findings reveal that the obligation to provide child maintenance remains attached to the father even after divorce, while the maintenance rights of former wives depend on the type of divorce and the conditions of the marital relationship. In judicial practice, several problems remain, including regulatory disharmony, disparities in judges' decisions, unclear standards for determining maintenance amounts, and weak enforcement mechanisms. Differences in regulations concerning the age limit of children and the determination of maintenance amounts often create legal uncertainty and weaken the protection of women and children after divorce. This study proposes a reformulation through the harmonization of regulations, the establishment of national standards for child maintenance based on the father's income and the child's actual needs, the strengthening of former wives' maintenance rights, and the development of more effective enforcement mechanisms. These reforms are expected to create a more just, effective, and protective family law system for women and children after divorce in Indonesia.